Petunjuk Penggunaan Alat Laboratorium Tanah dan Agroklimat dengan Fitur Stiker Quick Respone Code (Qr Code) - Endang Sulistyorini; Kirana Nugrahayu Lizansari; Widia Eka Putri (Fakultas MIPA UNM, 2022)
Abstract. Laboratory management is an important thing where the laboratory is a facility or as a place that can be used to apply a scientific theory. Labor managers usually print documents on A4- size paper and paste them next to laboratory tools. This causes documents to be damaged quickly, can reduce aesthetics, and not suitable for small laboratory tools. The purpose of making this QR- Code sticker, the author was designed to serve laboratory users and may provide digital information and materials to laboratory users to acquire knowledge.The process of making QR-Code was conducted for 2 months, from August to September 2021.QR-Code manufacturing stages were inventory of laboratory tools, inputting documents into Google drive, testing with blackbox methods and attaching QR-Code stickers to laboratory tools. The results obtained of QR-Code stickers are fliyer and QR-Code stickers taped to several soil and agroclimat laboratory tools, it is hoped that the laboratory management system can be improved better